2021
DOI: 10.1111/cdev.13567
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pathways Between Infant Gestures and Symbolic Actions, and Children’s Communicative Skills at Age 5: Findings From the All Our Families Pregnancy Cohort

Abstract: Using data from the All Our Families study, a longitudinal study of 1992 mother-child dyads in Canada (47.7% female; 81.9% White), we examined the developmental pathways between infant gestures and symbolic actions and communicative skills at age 5. Communicative gestures at age 12 months (e.g., pointing, nodding head "yes"), obtained via parental report, predicted stronger general communicative skills at age 5 years. Moreover, greater use of symbolic actions (e.g., "feeding" a stuffed animal with a bottle) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
(112 reference statements)
2
2
0
Order By: Relevance
“…A related possibility is that, at this young age, infants do not use gestures to compensate for lexical retrieval difficulties. As found in previous studies of monolingual children (Blake et al, 2003;Morin-Lessard et al, 2021;Özçalışkan et al, 2017), we generally observed positive correlations between communicative gestures and vocabulary size. Thus, at this age, gesture repertoire appears to develop alongside stronger verbal language skills, rather than compensating for weaker skills.…”
Section: Discussionsupporting
confidence: 90%
“…A related possibility is that, at this young age, infants do not use gestures to compensate for lexical retrieval difficulties. As found in previous studies of monolingual children (Blake et al, 2003;Morin-Lessard et al, 2021;Özçalışkan et al, 2017), we generally observed positive correlations between communicative gestures and vocabulary size. Thus, at this age, gesture repertoire appears to develop alongside stronger verbal language skills, rather than compensating for weaker skills.…”
Section: Discussionsupporting
confidence: 90%
“…This drove mothers to provide more symbolic feedback. Our results may explain previous results that associated gestures with the growth of symbolic skills (Marentette et al., 2016; Miller et al., 2020; Morin‐Lessard et al., 2021; Orr, 2018). Overall, this study determined that maternal responses are dynamic in many respects.…”
Section: Discussionsupporting
confidence: 88%
“…Importantly, these behavioral changes have been linked to later language abilities, including productive vocabulary and vocabulary growth up to 30 months of age ( Brooks and Meltzoff, 2008 ; Kuhl et al, 2008 , 2005 ; Morales et al, 2000 , 1998 ; Morin-Lessard et al, 2021 ; Rivera-Gaxiola et al, 2005 ; Singh et al, 2012 ; Tsao et al, 2004 ), language and preliteracy skills ( Cardillo, 2010 ; Cardillo Lebedeva and Kuhl, 2009 ), general communication skills at 5 years of age ( Morin-Lessard et al, 2021 ), and expressive grammar skills at 6 years of age ( Zhao et al, 2021 ). Thus there is strong evidence that these behaviorally observed changes are important for the development of later, more advanced language skills.…”
Section: Introductionmentioning
confidence: 99%